Religious identity and workplace discrimination: A national survey of American Muslim physicians. Issue 3 (2nd July 2016) - Padela, Aasim I.; Adam, Huda; Ahmad, Maha; Hosseinian, Zahra; Curlin, Farr
ABSTRACT: Background: Invidious discrimination is unreasonable and unethical. When directed against patients, such discrimination violates the respect for persons at the heart of bioethics. Might such discrimination also be directed at times toward physicians themselves? Studies of workplace discrimination have largely focused on race and gender, with few examining whether religious identity attracts discrimination. Muslim physicians from diverse backgrounds comprise 5% of the U.S. physician workforce and, given the sociopolitical climate, may face anti-Muslim discrimination in the workplace. We assessed the prevalence of perceived religious discrimination and its association with measures of religiosity through a national survey of American Muslim physicians.Methods: A questionnaire including measures of religiosity, perceived religious discrimination, religious accommodation at the workplace, and discrimination-related job turnover was mailed to 626 Islamic Medical Association of North America members at random in 2013.Results: Two hundred fifty-five physicians responded (41% response rate). Most were male (70%), South Asian (70%), and adult immigrants to the United States (65%). Nearly all (89%) considered Islam as the most or a very important part of their life, and most (63%) prayed five times daily; 24% reported experiencing religious discrimination frequently over their career, and 14% currently experience religious discrimination at work. After adjusting for personal and practice characteristics, respondents for whom religion was most important had greater odds of experiencing religious discrimination at their current workplace (OR 3.9, p < .01). Sixteen respondents reported job turnover due to religious discrimination, of whom 12 rated religion as the most important part of their life.Conclusions: A significant minority of Muslim clinicians experience religious discrimination at work, and particularly those for whom their religion is most important. Further research is needed to undergird data-driven programs and policies that might reduce invidious, religion-directed discrimination in the health care workplace.